The catalogues of the Pitt-Rivers Museum, Farnham, Dorset - Thomspson, Michael
The beautifully illustrated catalogues of Lieutenant General Pitt-Rivers collections at Farnham have recently been presented to the University of Cambridge Ñ where they will be in the public domain for the first time. The background to the collections and their catalogues is an intriguing story, showing the precision and detail demanded by Pitt-Rivers for his Farnham Museum. We are pleased to present some examples here, printed in colour and showing the range of the Victorian collector par excellence.